Development Study of T-Z Curve Generated from Kentledge System and Bidirectional Test - Nisa Utami Rachmayanti; Paulus Pramono Rahardjo (Kadiri University, 2021)
Pile loading tests to check the bearing capacity to support large loads. We can also use it to measure its deflection under lateral load. There are two tests: the axial static pile load test (Kentledge) and the two-directional static pile load test (Bidirectional). T-Z curve as the result analysis based on the instrumented pile test data describes the load distribution and mobilized skin friction along with the pile. Numbers of Vibrating Wire Strain Gauge (VWSG) mounted in several depths of the bored pile and two tell-tale on top and toe of the pile used as primary data in this research. This research to determine the different distribution of mobilized skin friction. The pile from two different pile load test methods from the calculated t-z curve as the study developed from both methods of pile test. The research results that the kentledge system has bigger mobilized skin friction than in bidirectional test.